PENDUGAAN PERTUMBUHAN KEPITING BAKAU (Scylla serrata Forskal) DI PERAIRAN KARANGSONG, INDRAMAYU, PROVINSI JAWA BARAT - Iqra Putra Sanur; Sulistiono Sulistiono; Yonvitner Yonvitner; Dudi Muhammad Wildan; Ayu Ervinia (Fakultas Perikanan dan Ilmu Kelautan, 2021)
Mudcrab (Scylla serrata Forskal) is one of several dominant species in the fish production from Karangsong coastal waters, Indramayu Regency. However, effort to manage the mudcrab in the waters is still limited. This study aimed to estimate a growth of the mudcrab as a base for crab management at the waters. Monthly sampling of the crab in the study area was conducted according to fisherman catch using bamboo trap for 4 months (Juni-September 2013). Carapace width and weight were employed for calculating frequency distribution, growth pattern, and growth. Growth estimation of the crab was calculated using Von Bertalanffy equation. This study revealed that the carapace width of the mudcrab ranged of 60-138 mm (male), and 74-139 mm (females). Crab’s growth patterns of the mud crab was negative allometric, W = 0.0003L2.8793 (male) dan W = 0.003L2.3210 (female). Through analysis of growth parameter estimation, it was obtained the following equatiosn: Lt = 157.35 [1-e(-0.39(t+0.26)] (male), and Lt = 147.99 [1-e(-0.42(t+0.24)] (female).